2014
DOI: 10.1093/jxb/eru040
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration efficiency: new insights into an old story

Abstract: Producing more food per unit of water has never been as important as it is at present, and the demand for water by economic sectors other than agriculture will necessarily put a great deal of pressure on a dwindling resource, leading to a call for increases in the productivity of water in agriculture. This topic has been given high priority in the research agenda for the last 30 years, but with the exception of a few specific cases, such as water-use-efficient wheat in Australia, breeding crops for water-use e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
269
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 256 publications
(284 citation statements)
references
References 108 publications
11
269
3
1
Order By: Relevance
“…Our findings showed that tolerant genotypes produced higher yields under combined P and water stress, had higher TE under low P conditions, while the total amount of water used was similar compared with sensitive genotypes. These results add to a recent review that argues that high TE can indeed be related to higher grain yield (Vadez et al 2014). More research would be needed to understand the mechanisms underlying the TE differences occuring Fig.…”
Section: Transpiration Efficiencysupporting
confidence: 66%
See 1 more Smart Citation
“…Our findings showed that tolerant genotypes produced higher yields under combined P and water stress, had higher TE under low P conditions, while the total amount of water used was similar compared with sensitive genotypes. These results add to a recent review that argues that high TE can indeed be related to higher grain yield (Vadez et al 2014). More research would be needed to understand the mechanisms underlying the TE differences occuring Fig.…”
Section: Transpiration Efficiencysupporting
confidence: 66%
“…The setup allows to determine transpiration efficiency (TE, calculated as dry matter (DM) produced per kg of water transpired) to distinguish tolerant and sensitive genotypes (Ratnakumar and Vadez 2011;Vadez et al 2011a;. It is well known that TE depends on interactions between water and nutrient availability (De Wit 1958;Tanner and Sinclair 1983;Clarkson et al 2000;Vadez et al 2014), and is particularly affected by nutrient deficiency (Payne 2000). For Sahelian conditions, Sivakumar and Salaam (1999) reported a 84 % increase of water use efficiency in millet (WUE, grain yield per mm rain), of which TE is an important component, due to the addition of mineral fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from 'cosmetic' stay-green (retention of nonfunctional chlorophyll; see reviews (e.g. Thomas and Howarth 2000;Cha et al 2002)), there are basically two parallel streams of hypotheses explaining the maintenance of green leaves under water stress, one of which deals with the enhanced use of available N (Rajcan and Tollenaar 1999;Borrell and Hammer 2000;Borrell et al 2001;Bertheloot et al 2008;van Oosterom et al 2010b) and another one favouring an improved plant water use status Vadez et al 2011Vadez et al , 2014. Several quantitative trait loci (QTLs) contributing to stay-green phenotype expression under drought (Stages 1-4, Stages A and B) have been validated across different research groups (Tuinstra et al 1996(Tuinstra et al , 1997(Tuinstra et al , 1998Crasta et al 1999;Subudhi et al 2000;Tao et al 2000;Xu et al 2000;Kebede et al 2001;Sanchez et al 2002;Haussmann et al 2002;Hash et al 2003;Harris et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The increased value of Ci in T 3 seems to be because of in-efficiency of the photosynthetic incorporation of CO 2 . A tight link has been found between large differences in TE in several crops and attributes of plants that make them restrict water losses under high vapour-pressure deficits (Vadez et al 2014).…”
Section: Discussionmentioning
confidence: 99%